2023
DOI: 10.1136/bmjopen-2022-063297
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-pocket cost for medical care of injured patients presenting to emergency department of national hospital in Tanzania: a prospective cohort study

Abstract: ObjectiveWe aimed to determine the out-of-pocket (OOP) costs for medical care of injured patients and the proportion of patients encountering catastrophic costs.DesignProspective cohort studySettingEmergency department (ED) of a tertiary-level hospital in Dar es Salaam, Tanzania.ParticipantsInjured adult patients seen at the ED of Muhimbili National Hospital from August 2019 to March 2020.MethodsDuring alternating 12-hour shifts, consecutive trauma patients were approached in the ED after stabilisation. A case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Among the older adult injury population 88% were hospitalized, and 64% required surgery. This finding shows the increased demand for the healthcare system required to care for older adults, which is consistent with other studies that demonstrated high costs and resources required in older adult trauma care (45)(46)(47). Additionally, our study showed that the majority (60%) of older adults were paying out of pocket for their hospital bills and more than 80% had limited income due to their age and working abilities.…”
Section: Discussionsupporting
confidence: 91%
“…Among the older adult injury population 88% were hospitalized, and 64% required surgery. This finding shows the increased demand for the healthcare system required to care for older adults, which is consistent with other studies that demonstrated high costs and resources required in older adult trauma care (45)(46)(47). Additionally, our study showed that the majority (60%) of older adults were paying out of pocket for their hospital bills and more than 80% had limited income due to their age and working abilities.…”
Section: Discussionsupporting
confidence: 91%
“…All the participants described how trauma posed a major economic burden in their lives. The out-ofpocket costs, both direct and indirect, especially in LMICs like India, have been well established in literature (62)(63)(64)(65). Being able to return to some form of work was one of the critical outcomes within the economic challenges stated by most participants.…”
Section: Discussionmentioning
confidence: 99%
“…One solution to tackle the escalating costs is to raise premiums; however, implementing higher premiums without subsidies for lower income members would hinder efforts to expand coverage 29. The lower premium contribution options for voluntary enrolment may motivate individuals to purchase health insurance especially if OOP costs rise, especially as it could reduce catastrophic health expenditures 30. NHIF has also proposed developing a maximum premium cost for voluntary enrolment to increase marketability of private enrolment, suggesting that increases in primary contribution to address rising cost of care would face major resistance and limit new enrolment 15…”
Section: Discussionmentioning
confidence: 99%
“…29 The lower premium contribution options for voluntary enrolment may motivate individuals to purchase health insurance especially if OOP costs rise, especially as it could reduce catastrophic health expenditures. 30 NHIF has also proposed developing a maximum premium cost for voluntary enrolment to increase marketability of private enrolment, suggesting that increases in primary contribution to address rising cost of care would face major resistance and limit new enrolment. 15 Mobilising additional public funding to supplement the NHIF finances could alleviate the rising claims Open access costs negatively impacting coverage.…”
Section: Discussionmentioning
confidence: 99%